The Gendered Impact of COVID-19: How Indonesian Women are Disproportionately Affected - Iva Anabel; Bevaola Kusumasari (BUANA GENDER : Jurnal Studi Gender dan Anak, 2023)
Gender is not the forefront issue of the COVID-19 pandemic yet lessons from previous outbreaks have suggested that women are disproportionately affected during such crises. This paper aims to understand the gendered impacts of the pandemic in Indonesia and offer insights into the experiences of women during the pandemic. We collected 10 administrative and survey data from government agencies, international organizations, as well as private organizations to conduct a secondary data analysis on the gendered impact of COVID-19 in Indonesia. Women are found to be bearing the brunt during the COVID-19 pandemic namely employment disruption, the burden of unpaid domestic and care work, heightened risk of gender-based violence, as well as indirect health and wellbeing impacts which includes accessibility to sexual and reproductive health services and stress levels.